Immunogenomic Characteristics of Cell-Death-Associated Genes with Prognostic Implications in Bladder Cancer - Xu, Wenhao; Tang, Hai-Jia; Anwaier, Aihetaimujiang; Liu, Wangrui; Tian, Xi; Su, Jiaqi; Wei, Shiyin; Qu, Yuanyuan; Zhang, Hailiang; Ye, Dingwei (Frontiers in Immunology, 2022)
Clear cell renal cell carcinoma (ccRCC) is one of the most common malignant genitourinary cancers with high recurrence risk worldwide. Recently, multi-omics data facilitate obtaining a molecular landscape of tumor development, and were implemented to affect pathogenesis, phenotype, and prognosis of ccRCC. In this study, after screening for differential expressed microRNAs based on multiply datasets, we tested expression levels and prognostic value of miR-187-3p in ccRCC samples, and transfected miR-187-3p mimics or negative controls into ccRCC cells. Up-regulation of miR-187-3p restrains proliferation, migration and promotes apoptosis ability in human ccRCC A498 and 786O cells. In addition, Luciferase reporter assay revealed that miR-187-3p directly targets LRFN1-3’-UTR and negatively modulates LRFN1 expression. LRFN1 rescues proliferation and invasion capacities after miR-187-3p mimic transfection in vitro and in subcutaneous xenograft models. We further performed deep-sequencing technology and bioinformatics analyses to evaluate the biological functions and potential clinical implications of LRFN1 expression in ccRCC. Interestingly, LRFN1 could serve as an independent and potential biomarker for prognosis in over 1,000 patients with ccRCC from multiply independent cohorts. Besides, the up-regulated LRFN1 expression prominently promoted intra-tumoral heterogeneity and immune-infiltrating microenvironment, represented by elevated M2 macrophage infiltration, CD8+ T cells activity and PD-L1 expression. In conclusion, this study revealed the tumor-specific and immunological role of miR-187-3p/LRFN1 axis in the progression and reshaping of tumor immune microenvironment of ccRCC.